QUALITY OF LIFE IN CHILDREN WITH HIRSCHSPRUNG'S DISEASE AFTER SURGERY DE LA TORRE-ORTEGA - Akilov Khabibulla Ataullaevich.; Khabibulla Ataullaevich Akilov; Umidzhon Shokirovich Mamajanov; Mirzakarimov Bakhrom Halimzhonovich.; Toshboev Sherzod Olimovich (Scholar Express Journals, 2022)
The article presents the results of the study of functional activity and quality of life in children with Hirschsprung's disease operated on using the improved DeLaTorre-Ortega method and the classical Soave-Lenyushkin method. Quality of life of operated children was assessed using the adapted PedsQL™4.0 scale, which included a total of 21 questions assessing physical, emotional, social, and role functioning. Analysis of quality of life in children with Hirschsprung's disease showed a significant increase in all scales when the improved DeLaTorre-Ortega procedure was performed, up to 84.1-92.3%, with a change in the total score from 52.8±10.0 to 70.4±6.4 (t=6.79; p <0.001) in relation to the healthy children group>
Keywords: Hirschsprung's disease; quality of life; functional activity; children